Accreditation document tracking system using Scrum approach - Shanti Faridah Salleh; Hamimah Ujir; Rohana Sapawi; Hashimatul Fatma Hashim (International Journal of Evaluation and Research in Education (IJERE), 2020)
Document tracking which involves recording and monitoring the movement of documents has been a time-consuming task for staff. Dislocation and overlooking of the timeline have always been the problems in document control. An effective tool such as a web-based system is the easiest way to be implemented in the workplace. The Accreditation Document Tracking System (ADTS) is designed to monitor the movement and timeline of the document from a department to another department throughout the accreditation process efficiently. The main objective of this project is to develop a system that can track the location of a document and its status of submission at every stage. This advantageous system is developed through scrum approach, which is the most widespread agile methodology used in the industry. It offers flexibility and simplicity to the system developer in upgrading the system. Furthermore, the Unified Modelling Language (UML) is used to describe the interaction between user and proposed system. UML consists of three visual diagrams: (i) Use case diagram, (ii) activity diagram, and (iii) sequence diagram. By following each stage of the diagrams, the proposed system is able to be developed in order to achieve the objective of this project within within the university as well Malaysian Qualification Agency (MQA) and Ministry of Higher Education (MOHE).